The significance of the second cave episode in Jerome"s Vita Malchi - Kritzinger, Jacobus P. (HTS teologiese studies, 2014)
The authors argue that the second cave episode in Jerome’s Vita Malchi Monachi Captivi should, in view of the similarities with the first cave episode and the high incidence of literary devices employed in it, be recognised for its value in the interpretation of this vita. The book was intended as a defence of, and an exhortation to a life of celibacy and this dual purpose is clearly demonstrated in both episodes in which a cave is used as the setting. The second cave episode has been neglected in the scholarly debate about the purpose of the book and this article attempts to set the record straight.